2016
DOI: 10.4067/s0718-221x2016005000062
|View full text |Cite
|
Sign up to set email alerts
|

Surface wettability of Brazilian tropical wood flooring treated with He plasma

Abstract: This study investigated the effect of plasma treatment on changes of surface wettability of wood flooring from two Brazilian tropical species, Hymenaea spp. (rode locus) and Tabebuia spp. (lapacho). Wood flooring samples were plasma treated at low pressure in a helium atmosphere. Energy level was set at 100 W and four glow discharge times (5, 15, 30 and 45 s) were tested. Changes in wettability were investigated by measuring apparent contact angle, droplet volume and spreading contact area. The results showed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 22 publications
1
4
0
1
Order By: Relevance
“…Wood has been widely used by man throughout history. It has been directly related to problem solving such as housing, crossing of natural and/or artificial barriers, production of multiple-purpose vehicles, storage and transport of agricultural goods, manufacturing of furniture, utensils and sporting artifacts, among others uses (Toong et al, 2014;Araújo et al, 2016;Cademartori et al, 2016;Calil Neto et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Wood has been widely used by man throughout history. It has been directly related to problem solving such as housing, crossing of natural and/or artificial barriers, production of multiple-purpose vehicles, storage and transport of agricultural goods, manufacturing of furniture, utensils and sporting artifacts, among others uses (Toong et al, 2014;Araújo et al, 2016;Cademartori et al, 2016;Calil Neto et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Surface inactivation is another factor that influences the wettability of wood (Cademartori et al 2016). Wood components are bound together by molecular forces and wood binding sites become open and unstable when subjected to weather immediately after machining.…”
Section: Isolated Species and Sanding Analysis And Wettability Variablesmentioning
confidence: 99%
“…The wettability of wood is an important parameter to determine how the properties of a given wood's surface react to liquid (Siebra et al 2020). Wettability allows us to analyze the influence of several processes applied to wood, such as the effects of machining (Jankowska et al 2018, Rolleri et al 2016, thermal modification (Chu et al 2016, Lopes et al 2018, Santos and Goncalves 2016, film deposition by plasma technique (Cademartori et al 2016, Cademartori et al 2017, Fang et al 2016Peng and Zhang 2019, and varnish coatings (Darmawan et al 2018, Fonte et al 2019.…”
Section: Introductionmentioning
confidence: 99%
“…An interesting use of plasmas in wood surface modification is to oxidize its polymeric constituents to increase its surface free energy and wettability. Over the last 5 years, many workers explored this application to increase the interactions between wood and adhesives or coatings [176][177][178][179][180][181][182][183][184][185][186][187]. They found that using reactive carrier gases such as air and O 2 would lead to the creation of polar groups such as carboxyl and carbonyl at the surface of the treated wood, increasing its hydrophilicity and surface free energy.…”
Section: Plasma Modificationmentioning
confidence: 99%